2015
DOI: 10.1136/acupmed-2014-010752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcutaneous Electrical Nerve Stimulation on Rats with the Third Lumbar Vertebrae Transverse Process Syndrome

Abstract: 09073.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the third lumbar vertebrae transverse process syndrome model, EA at ST36 decreased mRNA expressions of IL-1β, TNF-α, and iNOS in third lumbar vertebrae muscle tissues. This result shows that EA can exert anti-inflammatory effects through downregulating the concentration of main proinflammatory cytokines and iNOS, which generates NO and inflammatory responses ( 88 ).…”
Section: Resultsmentioning
confidence: 98%
“…In the third lumbar vertebrae transverse process syndrome model, EA at ST36 decreased mRNA expressions of IL-1β, TNF-α, and iNOS in third lumbar vertebrae muscle tissues. This result shows that EA can exert anti-inflammatory effects through downregulating the concentration of main proinflammatory cytokines and iNOS, which generates NO and inflammatory responses ( 88 ).…”
Section: Resultsmentioning
confidence: 98%
“…A recent clinical study suggested that TEAS downregulates proinflammatory factors, such as C-X-C motif chemokine ligand 8 (CXCL8), IL-1, IL-6, TNF- α , and C–C motif chemokine ligand 2 (CCL2) in response to lower limb ischemia-reperfusion [ 16 ]. While, the animal study suggested that TENS inhibited the expression of IL-1 β , TNF- α , and inducible nitric oxide synthase (iNOS) [ 17 ]. As a type of acupuncture, TEAS combines TENS and acupoint therapy together [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…An intervertebral disc may fall out of its damaged outer rings due to medical condiververtibral dissection, often known as PLID or a sliding disc. When a person loses control of their bladder or bowels, they should seek emergency medical attention [6][7][8][9]. A herniated or ruptured disc in the lumbar spine may cause lower back and leg pain.…”
Section: Introductionmentioning
confidence: 99%